Development and Application of a Multiplex Reverse Transcription–Droplet Digital PCR Assay for Simultaneous Detection of Hepatitis A Virus and Hepatitis E Virus in Bivalve Shellfish - Maolin Wei; Jinfeng Wang; Yan Wang; Libing Liu; Xiangdong Xu; Jianchang Wang (Foods)
Foodborne viruses are significant contributors to global food safety incidents, posing a serious burden on human health and food safety. In this study, a multiplex reverse transcription–droplet digital PCR (RT-ddPCR) assay based on the MS2 phage as a process control virus (PCV) was developed to achieve the simultaneous detection of hepatitis A virus (HAV) and hepatitis E virus (HEV) in bivalve shellfish. By optimizing the reaction system and procedures, the best reaction conditions were selected, and the specificity, sensitivity, and reproducibility of the method were assessed. Additionally, the MS2 phage’s recovery rate was utilized as an indicator to evaluate the optimal sample nucleic acid enrichment method. The results indicated that the RT-ddPCR assay exhibited optimal amplification efficiency with primer concentrations of 900 nmol/L, probe concentrations of 350 nmol/L for HAV and HEV, and 500 nmol/L for MS2, an annealing temperature of 53.1 °C, an extension time of 90 s, and 45 cycles. Additionally, the developed multiplex RT-ddPCR assay demonstrated high specificity, with quantitation limits of 12.6, 8.9, and 7.8 copies/reaction being observed for HAV, HEV, and the MS2 phage, respectively. A total of 240 bivalve samples were analyzed, of which 4 were positive for HAV and 12 for HEV. The viral loads for HAV ranged from 3048 to 6528 copies/2 g, while those for HEV ranged from 3312 to 20,350 copies/2 g. This assay provides a vital tool for enhancing food safety monitoring.